O corpo político feminista sobre duas rodas: das ruas às redes - Maciel, Tereza Rafaella Cordeiro (2020)
The present work aims to understand, through the experiences of women and their social practices of urban mobility by bicycle, which dynamics make up "feminist lifestyles" based on activism on and through bicycles nowadays. The research privilegies the analysis of the experiences of violence, resistances and sororities experienced by women "feminist cycloactivists" either in public spaces, in institutional areas or on digital social networks, understanding that the dynamics that make up this social movement interconnect themselves in these three dimensions. Reporting the analysis, the qualitative research is based on an approach composed of three research fronts in concomitance: (1) an intersectional feminist sociological analysis, supported by a white, black and Latin feminist literature together, which aims to highlight aspects of gender, race, class, sexuality, geographical location, age, culture, etc. (2) Parallel to this perspective, add an investigation is added about the relationship between Body and Power, having as theoretical reference authors such as Judith Butler and Michel Foucault, closely with the use of Bourdieu's concept of habitus in order to understand more specifically how develops what calls political feminist body on two wheels develops and how this body, then on, acquires an activist lifestyle and empowerment status when it is imposed on the streets. (3) Finally, it also joins the two theoretical-methodological processes of investigation research mentioned above, a relational analysis between micro and macro realities, with emphasis on a more accurate look at the developments of those are on the margins creating alternatives to presented social reality. In order, the research guides the bourdieu field theory and the perspective of Bennett & Peterson's scene concept (2004) to have a broad view of the phenomenon in the local, translocal and transnational/virtual dimensions, the last, in turn, being approached in depth, from the concept of cyborg bodies (HARAWAY, 2009), ending the cycle with the perspective of movement formation through networks.